Alcohol Consumption and Self-Regulation - Mullan, Barbara (Springer, 2013)
Research to date mostly supports a relationship between self-regulatory capacity (and in particular executive function) and alcohol consumption. This chapter explores the nature of this bi-directional relationship, in particular the roles of different types of executive function in different stages or modes of alcohol consumption, the findings of laboratory- and community-based research, the effectiveness of chapter and cognitive measures of self-regulatory capacity, measurement issues and interventions targeting self-regulation in alcohol studies. The diverse research in this area suggests that further interventions targeting self-regulatory capacity are warranted in the alcohol literature, and with preliminary research already existing, population level interventions would be useful.